2015
DOI: 10.3345/kjp.2015.58.10.374
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis as an important ocular sign to help early diagnosis in Kawasaki disease

Abstract: PurposeIncomplete Kawasaki disease (KD) is frequently associated with delayed diagnosis and treatment. Delayed diagnosis leads to increasing risk of coronary artery aneurysm. Anterior uveitis is an important ocular sign of KD. The purpose of this study was to assess differences in laboratory findings, including echocardiographic measurements, clinical characteristics such as fever duration and treatment responses between KD patients with and those without uveitis.MethodsWe conducted a prospective study with 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
1
31
0
4
Order By: Relevance
“…Coronary artery lesions (CAL) are one of the most important complications of this disease. Ocular involvement in this disease is characterized by non-exudative conjunctivitis and anterior uveitis [2]. Posterior segment involvement is rare; however, recent studies have shown the involvement of the ocular posterior segment in the acute phase of Kawasaki disease [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery lesions (CAL) are one of the most important complications of this disease. Ocular involvement in this disease is characterized by non-exudative conjunctivitis and anterior uveitis [2]. Posterior segment involvement is rare; however, recent studies have shown the involvement of the ocular posterior segment in the acute phase of Kawasaki disease [3,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…11,16 Tedaviye başlamadan önce dikkate alınması gereken en önemli şey gecikmiş tedavinin koroner arter komplikasyonu ile ilgili olmasıdır. Bu nedenle erken tanı ve tedavi, koroner arter komplikasyonlarını azaltmak için daha önemli hâle gelmektedir.…”
Section: Resi̇m 3unclassified
“…Buradaki en önemli etken, inkomplet KH'deki tanı ve tedavinin gecikmesi olarak gösterilmekte-dir. 11,16,17 Tanı için öncelikle, beş günden uzun süren ateşli hastalarda ve/veya ateş odağı bulunduğu hâlde uygun tedaviye dirençli olan hastalarda bu hastalık-tan şüphe etmek ve kardiyak etkilenme açısından ekokardiyografik inceleme yapmak gerekmektedir.…”
Section: Resi̇m 3unclassified
See 2 more Smart Citations